Pointing Sensors and Sun Tracking Techniques - D. Fontani; P. Sansoni; F. Francini; D. Jafrancesco; L. Mercatelli; E. Sani (International Journal of Photoenergy)
Every optical system for sunlight concentration requires following the sun in its movement. The sun tracking method is essentially chosen on the base of collection geometry and optical system configuration. A simple, useful, and original technique to realise sun tracking is proposed. It is based on a double guiding system using two complementary procedures. A passive tracking device performs a preliminary collector orientation. Then an active tracking system realises its fine positioning and adjustments exploiting an optical pointing sensor. The core of this active tracking device is the sun finder. Pointing sensors for fibre-coupled, CPV (Concentrating Photo voltaic), and linear collectors are presented, illustrating in detail the working principle and practical use. All sensors were optically characterised in laboratory, under controlled and reproducible conditions. Some field tests completed the experimentation evaluating the sensors performance in outdoor working conditions.